Factors related to the occurrence of typhoid fever in the residential population of Musi River, Southern Sumatra - Septina, Desy; Ardillah, Yustini (Universitas Gadjah Mada, 2022)
Purpose: This study aims to determine the factors related to typhoid fever occurrence in the Musi River residential area in Seberang Ulu Palembang. Methods: Using a proportional cluster sampling technique, this quantitative study uses a case-control design with a population of 106 samples in the Musi River suburb of Seberang Ulu. Data analysis carried out in this study was univariate, bivariate, and multivariate. Results: The results of the study of the incidence of typhoid fever in the population of the Musi River region in Seberang Ulu showed a low socioeconomic (p-value = 0.032), low education (p-value = 0.015), individual hygiene (p-value = 0,000), using the toilet (p-value 0.025), clean water quality (p-value = 0.034), garbage storage facility (p-value = 0.006), fecal leasing facility (pvalue = 0.018) is related to the incidence of typhoid fever, age, gender, occupancy density is not relationship with the incidence of typhoid fever Based on the results of multivariate analysis, the variable waste disposal facility is the most influential variable with the Odds Ratio 3.557; 95% CI 0.951-13,229. Conclusions: It can be concluded that the waste disposal facilities in the Musi River suburb in Seberang Ulu are still not good and have become a dominant factor influencing the incidence of typhoid fever. Hence, it is advisable to carry out outreach efforts to increase environmental awareness and provide garbage disposal infrastructure to meet the requirements of a healthy environment. We are also looking for trash transport officers to transport to temporary landfills.